The Photographer's Guide to Silver Efex Pro : Learn by Video (Learn by video., 2014)
"This critically-acclaimed interactive training program from Peachpit Press offers exceptional quality high-definition video to teach the fundamentals of Silver Efex Pro, the premiere black and white post-processing software from Google's Nik Collection. Including 1.5 hours of tutorials, this Learn by Video features instructor and professional photographer Sean Arbabi. In this video, Sean first presents a great introduction to black and white photography, including a discussion of what kinds of scenes work best for conversion to black and white; how a wide tonal range and contrast contribute to the effect of the image; and how the storied Zone System can be put to use in your Silver Efex Pro work. Sean covers everything: importing images; viewing and comparing images; setting preferences that work best for you; the power of presets in Silver Efex Pro; both global and local adjustments (with very powerful Control Point technology); how Silver Efex Pro's color filters can be used to enhance the image; how Film Types can add to the mood and feeling of an image; and the final toning and burning to the image, as well as how to add characteristic borders to your image to polish your photo's final look."--Resource description page.